Phytochemicals act holistically to enhance host defenses during poultry coccidiosis - Inkyung Park; Hyoyoun Nam; Sripathy Ravichandran; Emma H. Wall; Hyun S. Lillehoj (Poultry Science)
This study was conducted to investigate the effects of a phytochemical mixture containing full spectrum cinnamon, clove, and oregano essential oils (CCO) on the growth performance, intestinal immunity, and intestinal integrity of broilers infected with coccidiosis. In chicken macrophage cells (CMCs), inflammation was induced with 1.0 µg/mL LPS, followed by stimulating with CCO at three concentrations (1.0, 10.0, and 100 µg/mL) and measuring the gene expression levels of IL-1β and IL-8. In chicken intestinal epithelial cells (IECs), CCO was added and cultured, and the gene expression levels of occludin, ZO-1, and MUC2 were measured. In the in vivo experiment, one hundred and twenty male broiler chickens (0-day-old) were allocated into three treatment groups: (1) basal diet without infection (NC), (2) basal diet with E. maxima infection (PC), and (3) CCO at 4.5 mg/kg feed with E. maxima infection (CCO). Body weight (BW) was measured on days 0, 7, 14, 20, and 22. PC and CCO groups were orally infected with E. maxima on day 14. Jejunal samples were collected on day 22 to conduct gene expression analysis of cytokines, TJ proteins, and antioxidant enzymes. CCO significantly decreased IL-1β and IL-8 in CMCs and increased ZO-1 and MUC2 in IECs in a dose-dependent manner. In the E. maxima-infected groups, dietary CCO tended to mitigate BW loss due to infection. Upon infection, proinflammatory cytokines were suppressed in the CCO group compared to the PC group. Dietary CCO also increased the expression of occludin and JAM-2 in the jejunum. However, CCO did not reduce the oocyst number in coccidiosis-infected chickens. These results suggest that dietary CCO supplementation may improve intestinal immunity and permeability, helping to reduce productivity losses in E. maxima-infected broilers through gut physiological responses, rather than direct antimicrobial effects. These results show the advantage of using in vitro screening based on host-mediated responses, and not on direct pathogen killing, when exploring new phytochemicals to mitigate disease response to reduce economic losses due to coccidiosis.